2021
DOI: 10.1590/0102-311x00170920
|View full text |Cite
|
Sign up to set email alerts
|

Acesso a medicamentos e cooperação Sul-Sul: um estudo de caso de negociação conjunta de preços na América do Sul

Abstract: Resumo: Este artigo tem como objetivo analisar a negociação conjunta de preços de medicamentos de alto custo, que iniciou em 2015 nos âmbitos do Mercado Comum do Sul (Mercosul) e da União de Nações Sul-Americanas (Unasul), com a participação da Organização Pan-Americana da Saúde (OPAS). Apresenta-se como um estudo de caso, baseado em pesquisa documental e entrevistas em profundidade, que descreve a primeira etapa presencial do processo de negociação de preços conduzido pelo Comitê Ad Hoc de Negociação de Preço… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is pointed out that the difficulties in access to public health care are motivated by the social inequalities that are present in Brazilian society and that affect, above all, the most vulnerable segments of contemporary society. 22 A study developed in Germany, France, and the United Kingdom also evidenced that users with economic difficulties were the ones who faced greater obstacles in the use of the health services they sought. 23 Research developed in Argentina, with indigenous communities, also inferred that there are disadvantages in access to health and information for people with socioeconomic resources deficit living with diabetes.…”
Section: Right To Health In Users With Diabetesmentioning
confidence: 99%
“…It is pointed out that the difficulties in access to public health care are motivated by the social inequalities that are present in Brazilian society and that affect, above all, the most vulnerable segments of contemporary society. 22 A study developed in Germany, France, and the United Kingdom also evidenced that users with economic difficulties were the ones who faced greater obstacles in the use of the health services they sought. 23 Research developed in Argentina, with indigenous communities, also inferred that there are disadvantages in access to health and information for people with socioeconomic resources deficit living with diabetes.…”
Section: Right To Health In Users With Diabetesmentioning
confidence: 99%
“…This brings us significantly closer given that one of the greatest advances on the regional agenda in South America in recent years has been in the area of medicines, through the price bank and joint purchases of high-cost medicines, which have been a great opportunity for strengthening national and regional capacities. 5 , 6 Regarding the Medicines Price Bank of UNASUR, the Group on Universal Access to Medicines of UNASUR, developed a database with the prices of drugs in all the countries of the region as a negotiating strategy. This information was a very useful tool during negotiations with the pharmaceutical companies.…”
mentioning
confidence: 99%
“…This information was a very useful tool during negotiations with the pharmaceutical companies. About, the joint negotiation of prices for high-cost medicines, this initiative contributed to save millions of dollars in joint purchases of medicines for hepatitis C. 5 , 6 Studies have shown that the articulation of countries through regional integration mechanisms such as UNASUR and the Southern Common Market, and with the participation of other regional instances, such as Pan-American Health Organization, led to economic savings in terms of drug purchases, with strategies of complementarity between the mechanisms, contrary to the overlapping of initiatives, such as the Joint Purchases of Medicines. Unfortunately, some of these processes were cut short due to the dissolution of UNASUR.…”
mentioning
confidence: 99%